Multifaceted Impact of MicroRNA 493-5p on Genome-Stabilizing Pathways Induces Platinum and PARP Inhibitor Resistance in BRCA2-Mutated Carcinomas - Meghani, Khyati (Cell Rep, 2018)
BRCA1/2-mutated ovarian cancers (OCs) are defective in homologous recombination repair (HRR) of double-strand breaks (DSBs) and thereby sensitive to platinum and PARP inhibitors (PARPis). Multiple PARPis have recently received US Food and Drug Administration (FDA) approval for treatment of OCs, and resistance to PARPis is a major clinical problem. Utilizing primary and recurrent BRCA1/2-mutated carcinomas from OC patients, patient-derived lines, and an in vivo BRCA2-mutated mouse model, we identified a microRNA, miR-493-5p, that induced platinum/PARPi resistance exclusively in BRCA2-mutated carcinomas. However, in contrast to the most prevalent resistance mechanisms in BRCA mutant carcinomas, miR-493-5p did not restore HRR. Expression of miR-493-5p in BRCA2-mutated/depleted cells reduced levels of nucleases and other factors involved in maintaining genomic stability. This resulted in relatively stable replication forks, diminished single-strand annealing of DSBs, and increased R-loop formation. We conclude that impact of miR-493-5p on multiple pathways pertinent to genome stability cumulatively causes PARPi/platinum resistance in BRCA2 mutant carcinomas.